2023-2024 - Where we are and where we want to be! - Tiago Torres; Margarida Gonçalo (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
For the Portuguese Journal of Dermatology and Venereology, 2023 was a year characterized by its growth, the quality of the published manuscripts, and the continuous collaboration of the journal's reviewers.